Impacts of COVID-19 on malaria elimination strategies in Asia: A scoping review - Arisanti, Risalia R.; Saputri, Grace ND.; Ahmad, Riris A.; Utarini, Adi (Narra Sains Indonesia, 2024)
The global malaria program has faced setbacks due to disruptions in health services caused by COVID-19 pandemic. Despite these challenges, Asia that primarily comprised of low and middle-income countries (LMICs), continues to make strides towards malaria elimination. This scoping review explored the impact of the COVID-19 pandemic on malaria control programs in Asian countries with varying levels of malaria endemicity. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was applied to search for articles published between January 2020 and May 2024 that examined the impact of COVID-19 on malaria control programs in Asia on six databases (PubMed, Scopus, Google Scholar, WHO COVID-19 Research Database, Garuda and Sinta). The findings of these articles were organized into five themes: epidemiology and surveillance, case management (including diagnosis and coinfection), vector control, prevention, and program management. Overall, 54 articles from countries with various endemicity levels were included. These studies focused on malaria epidemiology, surveillance, and case management, with few studies on vector control. The COVID-19 pandemic has affected malaria control differently in different regions. In malaria-free, low-, and high-endemic countries, malaria cases were reduced mainly due to strict public health measures such as travel restrictions, quarantines, and COVID-19-related stigma, which reduced clinic attendance. Conversely, increased malaria cases owing to increased imports, relapses of malaria cases triggered by COVID-19, social conflicts, and underreporting have contributed to this surge. The priority shift to COVID-19 has affected malaria centers, resulting in personnel shortages, budget limits, and an increased number of malaria cases and outbreaks. The pandemic has also spurred innovative malaria prevention methods, such as using social media to raise awareness in China. The COVID-19 pandemic has had a mixed impact on the number of malarial cases reported across Asia. The three main factors were travel restrictions, COVID-19-related stigma, and shifting priorities to COVID-19. Integrating malaria control and COVID-19 strategies, strengthening the healthcare system, developing flexible malaria control strategies during crises, and developing innovative solutions could mitigate these impacts.